Expression analysis and introgression of transcriptional factor (DREB1A) in tomato for cold tolerance - Ali, Shaukat; Kareem, Kiran; Zia, Muhammad Amir; Khan, Siffat Ullah; Shahzad, Armghan; Jalal-ud-Din; Ali, Muhammad (Journal of Pure and Applied Agriculture, 2023)
: Crop productivity is impaired by a wide range of abiotic stresses. Cold stress is the main factor that causes the decrease in productivity of tomato. Through genetic engineering, a single gene can be easily transferred with desired characteristics into local best performing varieties. CBF/DREB1 is the most effectively used gene family to engineer cold stress tolerance in tomato. The aim of this study was to focus on the transgene expression and inheritance pattern in segregating generation of tomato lines and impact of transgene in different genetic backgrounds. In this study, transfer of transgene through conventional breeding into two elite cultivars (BSX-935 and 95017) was carried out. The lines used for detection and confirmation of transgene were previously developed by genetic transformation with a construct containing the AtDREB1A gene driven by the stress-inducible promoter lip-9. Transformants of T4 generation were identified by PCR and were selfpollinated to generate T5 progeny. The confirmed transgenics were used to evaluate different morphological traits such as plant height, fruit size, number of fruit per plant and number of seeds per fruit compared with nontransgenic counterparts. By using Completely Randomized Design, non-significant differences were found between transgenics and their non-transgenics plants. To check the expression pattern in transgenic plants, reverse transcription polymerase chain reaction was done. Progenies of T5 transgenic lines were used as pollinators for introgression into two elite cultivars BSX-935 and 95017. Successful F1 hybrids were confirmed through molecular analysis. These F1 hybrids may be used as a source for development of cold tolerant nearly isogenic lines through backcross breeding program in future.